Identification of aroma, bioactive, and chemical compounds of red and black glutinous rice after processing using a rice cooker: Identifikasi senyawa aroma, bioaktif dan kimia beras ketan merah dan hitam setelah pengolahan menggunakan rice cooker - Kiay, Nancy; Riastutik, Desak Nyoman (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
Glutinous rice has different aroma compounds according to its type and variety. Aroma compounds are volatile, especially during the heating process, which causes the loss of some aroma components, alters the chemical composition, and reduces antioxidant activity. This study aimed to identify aroma compounds, chemicals, and antioxidant activity of red and black glutinous rice processed into rice using the rice cooker method. The parameters observed in this study included the identification of aroma compounds, bioactives consisting of total phenols, anthocyanins, and antioxidant activity. Chemical contents of red and black glutinous rice, including amylose content, water content, ash, fat, protein, and carbohydrates were aslo anaalyzed. The results showed that the aromas compounds found in red and black glutinous rice after cooking were dominantly hydrocarbons, aldehydes, and alcohols. The results of the study showed that the highest anthocyanins content and antioxidant activity were found in black glutinous rice, with values of 17.60 ± 0.78 mg/100g and 51.03 ± 1.01%. Meanwhile, the results of chemical parameter observed showed significant differences (p< 0.05) in water content and ash content, with the highest values in black glutinous rice, namely 43.47 ± 0.01% for water and 0.96 ± 0.02% for ash. Red and black glutinous rice had protein contents of 4.84±0.64% and 4.76±0.03%, respectively, and fat contents of 1.44±0.03% and 1.14±0.01%, respectively. Carbohydrate contents were 51.93±0.06 % and 49.71±0.03 %. In comparison, the amylose content of red and black glutinous rice were 1.18 ± 0.06% and 1.22 ± 0.04%. Black glutinous rice processed using a rice cooker has a higher nutritional content compared to that of red glutinous rice.